Epidemiological Diagnosis of Diseases and Social Determinants in a Rehabilitation Center in Ecuador, 2023 - Marco Eduardo Herrera Herrera. MD., MPH, Alejandra María Corona-Romero (South Eastern European Journal of Public Health, 2025)
It is proposed to carry out an epidemiological diagnosis of NCDs: Diabetes Mellitus, Arterial Hypertension, Overweight, and their relationship with several social determinants of health in the Sierra Centro Norte Cotopaxi Regional Social Rehabilitation Center, belonging to the Zonal Coordination 3 of Ecuador, during the year 2024. The relevance of this research lies in several fundamental aspects, among these, Diabetes Mellitus, Arterial Hypertension and Overweight, are chronic health conditions that represent a significant challenge for public health systems worldwide. These chronic diseases not only affect the quality of life of individuals, but also impose a considerable economic burden on health systems and society at large. In Ecuador, specifically in the area of intervention for the study, the prevalence of these conditions has not been widely documented, underscoring the need for a clear and accurate diagnosis. As the main contribution to knowledge in public health, epidemiology and social sciences. By integrating the analysis of chronic health conditions with the study of social determinants, this paper proposes a holistic and multidisciplinary approach to understanding and addressing the various problems of public health. This perspective is pertinent in the realm of health in rehabilitation centers where health and social factors often interact in complex ways. Finally, the results of the study will have important practical implications by identifying trends and correlations between chronic diseases and social determinants of health in the specific context of Zonal Coordination 3, and more targeted and effective interventions can be developed. Not only will this benefit affected individuals and their families, but it can also contribute to the efficiency and effectiveness of public health programs in Ecuador..